Tradisi Ompangan Tengka Walimatul Ursy Perspektif Urf dan Maslahah Mursalah: (Studi Kasus di Desa Karduluk, Kec. Pragaan, Kab. Sumenep) - Riadi, Affan (Prodi HKI IAI Miftahul Ulum Pamekasan, 2023)
The tradition of Ompangan Tengka Wali>mat al-'Urs which is sometimes enlivened with entertainment, where this entertainment requires a sizable budget, this will lead to prolonged and accumulating debts, even the Ompangan Tengka debt is passed on to their children and grandchildren. The focus of this study (1) The reasons for the Karduluk community to preserve the Ompangan Tengka Wali>mat al-'Urs tradition (2) 'Urf's view of the Ompangan Tengka Wali>mat al-'Urs tradition (3) The approach used in this study is a descriptive- analysis. Data collection techniques used are interviews, observation, and documentation. Data analysis techniques were carried out by means of data reduction, data categorization, data analysis, drawing conclusions. To check the validity of the data the researcher uses triangulation. The results of this study found that (1) the Karduluk community preserved the Ompangan Tengka Wali>mat al-'Urs tradition as follows: First, traditions or ancestral heritage. Second, the strong social spirit of the Karduluk community. Third, long-term investment. Fourth, capital for the celebration of Wali>mat al-'Urs. Fifth, the actualization of Islamic religious recommendations. (2) Viewed from the perspective of 'Urf, the Ompangan Tengka Wali>mat al-'Urs tradition is categorized as follows: First, in terms of its object, the Ompangan Tengka Wali>mat al-'Urs tradition is 'Urf al-'Amali>. Second, in terms of coverage it belongs to 'Urf al-'Am. Third, in terms of its validity in syara', it is included in 'Urf al-Sahi>h.